Shifting from Private to Public Transport using a Duration-Based Modeling of a School-Based Intervention - 1. QUEIROZ, M.M.; Roque, C; Moura, F. (Transportation Research Record, 2020)
School commuting with public transportation (PT) and shifting away from private cars remains a challenge, especially for transport planners. From behavioral and cultural viewpoints, car dependence has not yet been reversed in many cities. Actions to promote the shift to PT should be multidisciplinary and multi-instrumental to increase PT adoption and achieve more sustainable mobility. There is a lack of strategic alignment between the different stakeholders involved in school commuting of children (parents, school, PT operators) and empirical studies sustaining the effectiveness of actions to shift away from the car. Moreover, PT behavioral aspects are still poorly researched from a marketing perspective. This research aims to help fill the gap by implementing actions related to the 4Ps of the marketing mix (product, place, price, promotion). Ten schools in the Lisbon Metropolitan Area were involved in those actions and then surveyed (1,760 survey participants) to evaluate the impact on their behavioral change, that is, to start going to school with PT. The study explores the impact of a set of marketing events on the time duration before children shift to PT when commuting to school, with a hazard-based duration model. Results suggest that to promote school commuting with PT, it is necessary to characterize the school community before commencing any mobility-oriented intervention, particularly concerning sociodemographic attributes and mobility patterns. These are critical information to design marketing actions better and to adapt and improve the quality of PT vehicles and services that operate to and from schools.